Impact of minor amounts of hydroperoxides on rhodium-catalyzed hydroformylation of long-chain olefins. Issue 7 (22nd March 2017) - Gerlach, M.; Abdul Wajid, D.; Hilfert, L.; Edelmann, F. T.; Seidel-Morgenstern, A.; Hamel, C.
Abstract : The influence of varying hydroperoxide concentrations in olefin feeds was systematically investigated in rhodium-catalyzed hydroformylation using a diphosphite ligand. Abstract : The effect of minor amounts of impurities on the course of chemical reactions is often overlooked. Analyzing commercial 1-dodecene feeds, hydroperoxides were identified as critical impurities. The influence of varying hydroperoxide concentrations in olefin feeds was systematically investigated, experimentally studying rhodium-catalyzed hydroformylation using a diphosphite ligand. A significant loss of n -aldehyde selectivity and linear-to-branched ratio ( l / b ) was observed for increasing hydroperoxide concentrations. Feeding of an additional ligand and/or purification of 1-dodecene restored the catalyst performance.